453 Introduction of A Novel Online Learning Platform Increases Junior Doctors Confidence Prior To Starting Trauma & Orthopaedic On-Calls. (12th October 2021) - Curtis, A; Foster, P; Mutimer, J
Abstract: Aim: Trauma and Orthopaedic (T&O) junior doctors are expected to manage on-calls involving a high volume of patients presenting with a wide variety of complex conditions. Despite this, many junior doctors feel poorly prepared at the start of their placements with individual hospitals providing variable levels of induction. We therefore aimed to provide a free 'Introduction to T&O on-calls' course for junior doctors. Method: The online platform 'Zoom' was used to provide 13 interactive lectures by T&O trainees and consultants over a single day in July 2020. In total, 280 UK junior doctors attended with 91.1% completing feedback. Pre- and post-course questionnaires were used to establish improved knowledge. Results: Only 7.4% of participants either had or were aware of a local trust induction covering T&O on-calls. The course had an overall satisfaction rating of 90%, with participants showing a 15.3% improvement in on-call knowledge from pre-course to post-course ( p <0.05). Prior to the course only 35% of participants felt prepared to perform an on-call which increased to 77% after the course. Almost all participants (90%) agreed that similar courses in other surgical specialties (General surgery (79%), Urology (60%), Vascular surgery (60%), ENT 55%)) which are commonly cross covered by junior doctors would be hugely beneficial. Conclusions: Our principal focus moving forward is to establish a formal national induction programme for T&O junior doctors that is recognised by the relevant T&O organisations. This will instil confidence in the junior doctors whilst achieving patient safety and excellence during busy T&O on-calls.